NOKIA'S MARKETING STRATEGIES IN INDIA - Daga, Nikunj (2007)
This research studies the marketing strategies of Nokia, a high technology company in a developing country India. The study attempts to check the role of marketing activities in success of Nokia in India. After studying the past of the company and the history of Indian mobile industry, Nokia's marketing strategies are examined through secondary resources. Then to check the effect on the consumers, semi-structured interviews of a few mobile phone dealers in India are taken. Here, interviews as a tool of qualitative research is adopted to create a deep understanding of the customers perceptions. To get a generalized view, mobile phone dealers are interviewed as they deal with many consumers and can give the opinion of the market as a whole. The findings advised that consumers preferred Nokia over all other brands due to features of the phone. Features such as user friendliness, rough and tough body, long life etc were believed to be the reasons of success. Though the marketing strategies have been aggressive, they were not the reasons for high market share of the company.